Edutainment-Based Comic Media to Improve Skills in Writing Historical Narrative Information - Efeline Nuzula Az Zahra; Panca Dewi Purwati; Trimurtini (Jurnal Edutech Undiksha, 2024)
Many students still struggle with low writing skills due to a lack of knowledge about writing. This research aims to develop edutainment-based comic learning media to improve historical narrative writing skills for fifth-grade elementary students. This type of research is development research using the Borg and Gall model and involves one expert in learning materials and one in learning media. The study's test subjects were 6 students from class 5B for a small-scale test and 25 students from class 5A for a large-scale test. Data collection methods included observation, interviews, questionnaires, documentation, and tests. The instruments used were questionnaires and test questions. Data were analyzed using qualitative and quantitative descriptive analysis techniques. The results showed that learning media validation by material experts scored 94% (very feasible) and by media experts scored 82.5% (feasible). The effectiveness of edutainment-based comic learning media was evident with an increase in the average student pretest and posttest scores in the skills aspect by 0.40, categorized as "medium." The questionnaire results and responses from teachers and students indicated that the media were very appropriate. In conclusion, comic media with edutainment innovation significantly improves student learning outcomes in writing skills and is suitable for use in elementary schools. This research has implications for enhancing the quality of teaching services and improving Indonesian language learning outcomes in elementary schools through the development of effective teaching media.